POLA KOMUNIKASI TRADISI DALAM KEHIDUPAN SUKU BADUY DI ERA DIGITAL - Nursatyo Nursatyo; Aos Yuli Firdaus; Febiyana Pratiwi; Risma Akhwat; Gilang Ramadhan; Kartika Sandhi; Wirdiyan Naufal; Yolti Veni Efendi (Universitas Baturaja, 2023)
The pattern of traditional communication of Baduy people in the digital era has changed slightly. The Baduy Luar people still maintain the authenticity of their traditions well, but do not close themselves to advances in digital technology. Meanwhile, Baduy Dalam community is completely untouched by technological advances at all. In this case, communication is a key factor to strengthen the cultural existence of Baduy people. This article was created to provide an overview of the traditional communication patterns of the Baduy tribe in the digital era. Data was collected through direct observation to the Baduy Luar community in Kanekes Village as well as interviews with several informants from the Baduy community including traditional wisdom called Jaro. The results of the study show that Baduy people, especially Baduy Dalam, are still able to maintain their cultural values ​​along with the use of digital technology, such as the use of smartphones and social media applications and digital banking. Even though digital technology has penetrated into the life of the Outer Baduy people, they are still able to maintain noble cultural traditions. This cannot be separated from the traditional communication pattern of the Baduy tribe which is linear top-down.